The Influence of Information Technology Utilization, Human Resource Competence, and Work Environment on Employee Performance at the Regional House of Representatives Secretariat of Buleleng Regency - Ni Luh Putu Eka Yudi Prastiwi; Ni Kadek Mika Suciandriani; Ni Made Widnyani (International Journal of Management Science and Information Technology, 2026)
This study examines the effects of information technology utilization, human resource (HR) competence, and the work environment on employee performance at the Secretariat of the Regional House of Representatives (DPRD) of Buleleng Regency. The study was prompted by fluctuations in employee attendance during 2025 despite the adoption of digital initiatives, including biometric attendance systems. A quantitative causal design was applied, involving 110 respondents selected from a population of 151 employees using disproportional random sampling. Data were collected through a structured questionnaire and analyzed using multiple linear regression with SPSS 25 after the required validity, reliability, and classical assumption tests were satisfied. The results show that information technology utilization (t = 2.094; p = 0.025), HR competence (t = 3.292; p = 0.001), and the work environment (t = 8.926; p < 0.001) each have a positive and significant effect on employee performance. The three predictors also have a significant simultaneous effect (F = 96.610; p < 0.001), with an Adjusted R² of 0.725, indicating that they jointly explain 72.5% of the variation in employee performance. The findings highlight the importance of integrating effective technology utilization with continuous competency development and a supportive work environment to strengthen employee performance and organizational effectiveness in public institutions.